A ranking of high‐resolution daily precipitation extreme events for the Iberian Peninsula. (9th May 2014) - Ramos, Alexandre M.; Trigo, Ricardo M.; Liberato, Margarida L. R.
Abstract A method for ranking daily precipitation events is presented based on the most comprehensive database of daily gridded precipitation dataset available for the Iberian Peninsula spanning from 1950 to 2008. The magnitude of an event is obtained after considering the area affected as well as its intensity in every grid point and taking into account the daily normalized departure from climatology. Different precipitation rankings are presented considering the entire Iberian Peninsula, Portugal and also the six largest river basins in the Iberian Peninsula.